Alternative Delivery Platforms for Expanding Evidence-based Mental Health Interventions for Youth in Sierra Leone: a Pilot Study. Issue 1 (2nd January 2023) - Desrosiers, Alethea; Freeman, Jordan; Mitra, Romita; Bond, Laura; Dal Santo, Leila; Farrar, Jordan; Borg, Ryan; Jambai, Musu; Betancourt, Theresa S.
ABSTRACT: Given the high rates of mental health problems and poor service access among youth in war-affected countries throughout Sub-Saharan Africa, incorporating evidence-based mental health interventions into alternative delivery platforms could improve service access in these settings. We conducted a randomized controlled pilot study with high-risk Sierra Leonean youth to investigate the feasibility of implementing the Youth Readiness Intervention (YRI), a cognitive behavioral and interpersonal therapy-based group intervention, within an employment promotion program (EPP) and preliminary effects of the YRI on mental health outcomes. Participants were 175 youth (females = 62%) ages 18–30 recruited via flyers and radio announcements. Participants were assigned to geographic clusters stratified by gender; clusters were randomized into YRI+EPP (n = 58) or EPP-only (n = 57). Statistically matched controls were recruited from comparable chiefdoms (n = 60). The 12-session YRI was delivered bi-weekly, following EPP completion. Qualitative findings indicated that the YRI was highly feasible and acceptable as integrated into the EPP. Mixed linear effects models showed promising trends. Compared with controls, both YRI+EPP and EPP-only males reported significantly reduced post-traumatic stress symptoms, and YRI+EPP reported marginally significantly reduced emotional regulation difficulties. EPP-only females reported significantly reduced functional impairment compared to controls. Findings suggest that the YRI can be feasibly implemented within an EPP. Integrating the YRI into existing delivery platforms may help increase access to mental health care in Sierra Leone and provide a leverage point for scaling up evidence-based mental health interventions in other low-resource settings globally. [Clinicaltrials.gov; NCT0360361; 5/18/18]